4th DLSU annual institutional service awards - De La Salle University, Manila (Animo Repository, 2015)
The University held the 4th DLSU Annual Institutional Service Awards in recognition of the services rendered by the teaching and non-teaching personnel. There were 138 teaching and non-teaching personnel who were honored during the event.